Nordic criminal justice in a global context : practices and promotion of exceptionalism - Jarle Christensen, Mikkel; Lohne, Kjersti; Hörnqvist, Magnus (Nordic studies in a global context, 2023)
"This book critically investigates Nordic criminal justice as a global role model. Not taking this role for granted, the chapters of the book analyse how Nordic approaches to criminal justice were folded into global contexts, and how patterns of promotion were built around perceptions that these approaches also had a particular value for other criminal justice systems. Specific actors, both internal and external to the region itself, have branded Nordic criminal justice as a form of 'penal exceptionalism' associated with human rights, universalistic welfare and social cohesion. The book shows how building and using the brand of Nordic criminal justice allowed stakeholders to champion specific forms of crime control across a variety of criminal justice areas in both domestic and international settings. The book will be of interest to scholars and students of criminal justice, international law and justice, Nordic and Scandinavian studies, and more widely to the social sciences and humanities"--
Keywords: Criminal justice, Administration of : Scandinavia; Human rights : Scandinavia; Crime prevention : Scandinavia; rikosoikeus; rikosoikeus : Pohjoismaat; Pohjoismaat; kansainvälinen rikosoikeus : Pohjoismaat; humanitaarinen oikeus : Pohjoismaat; prostituutio : Pohjoismaat; kriminologia : Pohjoismaat